THERAPEUTIC ACTIVITY OF ULUDAG UNIVERSITY ATATÜRK BALNEOTHERAPY AND REHABILITATION CENTER IN THE LAST DECADE - Alev Ay; M. Mustafa Ertürk; Ümit Bingöl; Lale Altan; Merih Yurtkuran (Archives of Rheumatology, 2004)
In Atatürk Balneotherapy and Rehabilitation Center, orthopedic, neurological and mainly rheumatological diseases are treated and rehabilitated on outpatient and inpatient basis. There are 31 beds for the outpatients who participate in daytime hospital and 24 beds for the inpatients. Physical therapy, training of the medical students, academical activity and scientific researches are carried on in the center. The objective is to report the therapeutic activity of the center in the last decade.